2020
DOI: 10.1038/s41416-020-01045-7
|View full text |Cite
|
Sign up to set email alerts
|

The nucleolar-related protein Dyskerin pseudouridine synthase 1 (DKC1) predicts poor prognosis in breast cancer

Abstract: Background Hypertrophy of the nucleolus is a distinctive cytological feature of malignant cells and corresponds to aggressive behaviour. This study aimed to identify the key gene associated with nucleolar prominence (NP) in breast cancer (BC) and determine its prognostic significance. Methods From The Cancer Genome Atlas (TCGA) cohort, digital whole slide images identified cancers having NP served as label and an information theory algorithm was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 57 publications
2
33
0
Order By: Relevance
“…For example, in contrast to our results on ECs, reports on prostate, hepatocellular carcinoma, and colorectal cancers showed that high DKC1 is commonly associated with an extensive tumour growth pattern [ 25 , 34 , 35 ]. Recently, Elsharawy et al showed that high DKC1 mRNA or protein levels in breast cancer associated with poor patient outcome and unfavourable clinicopathological characteristics [ 26 ]. In a recent study in breast cancer, DKC1 over-expression associated with unfavourable clinicopathological characteristics and poor outcome [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, in contrast to our results on ECs, reports on prostate, hepatocellular carcinoma, and colorectal cancers showed that high DKC1 is commonly associated with an extensive tumour growth pattern [ 25 , 34 , 35 ]. Recently, Elsharawy et al showed that high DKC1 mRNA or protein levels in breast cancer associated with poor patient outcome and unfavourable clinicopathological characteristics [ 26 ]. In a recent study in breast cancer, DKC1 over-expression associated with unfavourable clinicopathological characteristics and poor outcome [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Elsharawy et al showed that high DKC1 mRNA or protein levels in breast cancer associated with poor patient outcome and unfavourable clinicopathological characteristics [ 26 ]. In a recent study in breast cancer, DKC1 over-expression associated with unfavourable clinicopathological characteristics and poor outcome [ 26 ]. Two publicly available “Breast Cancer Gene-Expression Miner v4.3” [ 26 ] and TCGA breast cancer datasets revealed high DKC1 mRNA levels to significantly correlate with larger tumour size, higher tumour grades, and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations